ISSUES OF TEACHER SKILLS IN HIGH SCHOOL PRACTICE - Маҳкамова М. Ю. (Journals Park Publishing, 2023)
The article analyzes the issues of teacher skills in high school practice. It discusses the views of Eastern thinkers on the teacher, the requirements for modern lessons, the requirements for teachers today.